Mendongeng Melalui Jenis-Jenis Dongeng Untuk Anak Usia Dini - Martina Napratilora; Mardiah; Sophia Nurhaqia (Fakultas Keguruan dan Ilmu Pendidikan Universitas Islam Indragiri (UNISI), 2023)
Strorytelling contain values ​​that are beneficial for children. Storytelling activities are the best method for making children learn. Children often use their study time as they want. With the storytelling method, children will listen attentively because storytelling are very interesting for children. The aim of this writing is to find out how to tell storyteling through types storytelling for young learners. Storyteling has several types based on their content. These types are divided into six, namely legend, fable, myth, folklore, sage, humorous, traditional, futuristic, educational and therapeutic. All types of storytelling has different contents. Storytelling for children have several characteristics. Where, these characteristics are explained based on several aspects. These aspects are in the form of story content aspects, language aspects, presentation aspects, value aspects, and graphic aspects.